The effect of pre-existing antibody on the result of immunization of mice with human B cell lines and transfected mouse cell lines - Samuels, Lewis (1995)
Thesis (M.Sc.)--Memorial University of Newfoundland, 1995. Medicine Bibliography: leaves 148-154. In process